PENINGKATAN PERKEMBANGAN KEMAMPUAN MENYIMAK MELALUI MEDIA BUKU CERITA BERGAMBAR DI PAUD CAHAYA SUNGAI RAYA - Sustrilita, Sustrilita; Marmawi, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aimed to improve students’ listening skill troughthe media story book picture on PAUD Cahaya Desa Kapur Sungai Raya.This research is conductedby a teacher with her priend. The number of the students are there in this research 15, consist of lo girls and boys.This research is conducted with 2 cycles in 4 time of mecting and the media used in this research is story book picture.The understanding of media in learning is all of communication tools that can be used to deliver massage or information from the resource to the students where it can stimulate their mind, feeling, interest, and attention to contribute in learning activity. While listerning skill involve interprestation process and translating sound which is heard so that can have a certain meaning. Listening skill involve creative prosess which needs an attention and concentration in understanding the meaning of information. Tha can be given in this research are expected to be picture book media can be one way to improve the development of the ability to listen to children. Keyboard: Development of Listening Capabilities, Story Illustrated Book Media.